Oxidação direta de metano em metanol sobre cátions [oxo-Cu2+] em zeólitas Y e mordenita – Efeito da temperatura aplicada aos ciclos isotérmicos de ativação e reação - Picinini, Monize (2023)
It is expected that in the coming decades, natural gas, consisting mainly of methane, will become an important raw material in the industry to produce chemicals and intermediates. Thus, it is of great interest to develop processes for the direct oxidation of methane to methanol via more sustainable and cost-effective routes, which would also reduce methane emissions to the atmosphere and, consequently, its impact as a greenhouse gas. Despite the scientific advances achieved in the study of this process, the breakage of the C-H bonds of the methane molecule remains a challenge, which has encouraged the development of highly active and selective catalysts. The studies have focused on exchanging zeolites with oxidized metallic cations to recreate the reactivity mechanism like that found in the enzyme methane monooxygenase, which converts methane to methanol under atmospheric conditions of temperature and pressure. In the discussed context, the objective of the work was to study the direct oxidation of methane to methanol over zeolites Y and mordenite exchanged with copper oxo-cations, analyzing the influence of the zeolitic structure and the activation conditions on the formation, nature, and activity of the generated species, as well as the conditions related to the methane reaction. The activated Cu-zeolites were characterized by energy-dispersive X-ray spectroscopy, X-ray diffraction, nitrogen physisorption, scanning electron microscopy, hydrogen, and methane temperature-programmed reduction, and in situ Fourier transform infrared spectroscopy by transmission mode. In order to determine the active species generated during activation and their subsequent consumption during methane reaction, both operated isothermally, in situ ultraviolet-visible diffuse reflectance spectroscopy analysis was performed. All the studied Cu-zeolites were able to convert methane to methanol. The activity profiles of the zeolite Y and mordenite were associated with the nature of the generated active copper species and their reaction temperature with methane. The in situ DRS-UV-Vis spectra showed bands related to dimeric and trimeric copper species in both the studied Cu-zeolites. Formation of monomeric active copper species was also observed for mordenite.